Grit-related Nursing Research Trends in the Korean Journal of Nursing - Kang, Se-Won (Advances in Social Sciences Research Journal, 2020)
This is a literature review to understand trends in grit-related nursing research published in the Korean Journal of Nursing. The literature search was targeted at articles published in Korean nursing journals including “grit” and “nursing.” Articles published in 2015-2020 were included. A total of 20 papers suitable for literature review were analyzed. These studies included 2 conceptual analysis studies, 3 tool development studies, and 15 descriptive research studies containing correlation and factor analysis were analyzed. For the target population, 6 studies targeting clinical nurses, 13 targeting nursing students, and 1 targeting patients were analyzed. In future grit-related nursing research, experimental study designs to apply grit should be used.